Adversity exposure and obesogenic food consumption in young children: The transgenerational role of emotion dysregulation. Issue 11 (21st May 2020) - Huffhines, Lindsay; Gusler, Stephanie; Jackson, Yo
Summary: Background: Childhood adversity is linked with unhealthy eating behaviours and obesity, but the mechanisms underlying this association are unclear, specifically the transgenerational behavioural precursors that develop in early childhood. Objective: To determine whether adversity predicts change in obesogenic food consumption through child emotion dysregulation, and whether caregiver emotion dysregulation modifies this association. Methods: Participants included 190 low‐income caregiver‐child dyads (mean child age = 4.31 years [SD = 0.85]). Cumulative lifetime adversity exposure was assessed via study‐created measure. The Difficulties with Emotion Regulation Scale and Emotion Regulation Checklist assessed caregiver and child emotion dysregulation, respectively. Children's obesogenic food consumption was assessed at two time points 6 months apart using a caregiver‐report measure: the Children's Eating Habits Questionnaire. Moderated mediation models were tested using autoregressive structural equation modelling. Results: Cumulative lifetime adversity was associated with child emotion dysregulation only when caregiver emotion dysregulation was high. Child emotion dysregulation in turn was associated with greater obesogenic food consumption 6 months later. Conclusions: Among young children with caregivers high in emotion dysregulation, cumulative lifetime adversity was linked to an increase in obesogenic food consumption through child emotion dysregulation.